A carbon accounting tool for complex and uncertain greenhouse gas emission life cycles. (September 2018) - Pichancourt, Jean-Baptiste; Manso, Rubén; Ningre, François; Fortin, Mathieu
Abstract: Software applications for life cycle assessment of greenhouse gas (GHG) emissions have become popular over the last decade. Their objective is to provide insight into how GHG emissions could be reduced in the sectors defined by the UNFCCC. However, boundaries between these sectors are not closed and current tools are not designed to represent this complexity or to assess the numerous sources of uncertainties. In this paper, we present CAT v1.0, software developed for managed forests in the LULUCF sector, but whose emission life cycle is linked to that of other sectors. While the structure of the software follows IPCC Guidelines, it also contains additional features such as an embedded Monte-Carlo error propagation technique and a user-friendly flux manager that allows for complex cradle-to-grave representations of the wood transformation industry. The flexibility of the software is illustrated through two case studies in northeastern France. Highlights: We developed a software platform to assess complex cross-sectoral GHG emission life cycles. CAT software provides a user-friendly interface that allows for the representation of complex life cycles. CAT uses the Monte Carlo technique for prediction uncertainty assessment. Two case studies of cradle-to-grave forestry supply chains exemplify CAT's potential. Managers can use CAT to design policies for achieving IPCC emission reduction targets.